2018
DOI: 10.1093/mnras/sty1737
|View full text |Cite
|
Sign up to set email alerts
|

Chromodynamical analysis of lenticular galaxies using globular clusters and planetary nebulae

Abstract: Recovering the origins of lenticular galaxies can shed light on the understanding of galaxy formation and evolution, since they present properties that can be found in both elliptical and spiral galaxies. In this work we study the kinematics of the globular cluster (GC) systems of three lenticular galaxies located in low density environments (NGC 2768, NGC 3115 and NGC 7457), and compare them with the kinematics of planetary nebulae (PNe). The PNe and GC data come from the Planetary Nebulae Spectrograph and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 75 publications
6
8
0
Order By: Relevance
“…For example, by recovering the galaxy kinematics using Planetary Nebulae, Cortesi et al (2013) showed that the disc of NGC 3115 is rotationally supported, but that the value of V/σ is lower than what found for spiral galaxies, suggesting that this galaxy is not simply a faded spiral. Similar results are found by studying the globular cluster population (Zanatta et al 2018) and integrated stellar light (Arnold et al 2011).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…For example, by recovering the galaxy kinematics using Planetary Nebulae, Cortesi et al (2013) showed that the disc of NGC 3115 is rotationally supported, but that the value of V/σ is lower than what found for spiral galaxies, suggesting that this galaxy is not simply a faded spiral. Similar results are found by studying the globular cluster population (Zanatta et al 2018) and integrated stellar light (Arnold et al 2011).…”
supporting
confidence: 86%
“…The same result was obtained by studying the globular clusters kinematics (Zanatta et al 2018). Reinforcing this point, Falcón-Barroso et al (2019) show, using CALIFA data of 300 galaxies across the Hubble sequence, that spiral galaxies hardly fade into S0s, unless specific conditions of light concentration, angular momentum and V/σ are satisfied (as for Sa galaxies).…”
Section: The Formation History Of Ngc 3115supporting
confidence: 66%
See 1 more Smart Citation
“…In the Milky Way, stars of accreted dwarf galaxies present different kinematics depending on their in-fall time, where recently acquired satellites have a larger difference to the galaxy systemic velocity and extend to larger radii (Rocha et al 2012). Similar results are found for the GC systems of NGC 1023 and NGC 3115 (Cortesi et al 2016;Zanatta et al 2018), where accreted GCs were encountered on the basis of their kinematics. In the case of NGC 1023, the majority of rejected GCs are consistent with having blue colours.…”
Section: Introductionsupporting
confidence: 65%
“…This is in agreement with Sil'chenko et al (2002) who also proposed a a merger-driven evolution in this galaxy. Zanatta et al (2018) in contrast, using the same approach, found that NGC 7457 has a disc dominated GC population. They claimed that, considering the estimated halo assembly epoch of this galaxy, along with the low density environment of this system and discy distribution of its GCs, a secular evolution scenario is the best mechanism to explain the observed properties of this system.…”
Section: Introductionmentioning
confidence: 91%